EKSPERIMEN MODEL MAKE A MATCH TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS BERDASARKAN GENDER PADA SISWA SEKOLAH DASAR - Yesi Tahnia; Nila Kesumawati; Nugroho N.A.D (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the make a match learning model on thecritical thinking skills of elementary school students based on gender. The methodused in this study is an experimental method with a posttest only control groupdesign. The subjects in this study consisted of two classes IV at SD Negeri 160Palembang, namely the experimental class given the make a match learningmodel and the control class with conventional learning. The instrument used in thisstudy was a descriptive test to measure student’s critical thinking skills. The resultsof data analysis using a two-way ANOVA test showed that (1) there was asignificant effect of the make a match learning model on students critical thinkingskills; (2) there was no difference in the average critical thinking skills ofmathematics based on student gender; (3) there was no interaction between themake a match learning model and gender on students’ critical thinking skills. Thus,the make a match learning model has proven effective in improving students’critical thinking skills without any gender differences.